2017
DOI: 10.1186/s12906-017-2032-5
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet mechanism of an herbal mixture prepared from the extracts of Phyllostachys pubescens leaves and Prunus mume fruits

Abstract: BackgroundBamboo (Phyllostachys pubescens) leaves and Japanese apricot (Mume fructus) fruit are traditionally recognized to be safe herbs broadly used for food and medicinal purposes in Southeast Asia. Our group previously explored their antiplatelet effects. This study was designed to confirm inhibition effects of PM21 (a 2:1 mixture of bamboo leaf extract and Japanese apricot fruit extract) on platelet aggregation and evaluate its potency to use as an herbal remedy to prevent and/or treat the diseases caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The platelet was isolated from SD rat aorta blood and mixed with sodium citrate (1:9, v/v) as previously described with some modifications (Son, Kim, Yang, Kim, & Cha, 2017). Briefly, anticoagulated blood was centrifuged (50 × g , 10 min) to obtain platelet‐rich plasma (PRP).…”
Section: Methodsmentioning
confidence: 99%
“…The platelet was isolated from SD rat aorta blood and mixed with sodium citrate (1:9, v/v) as previously described with some modifications (Son, Kim, Yang, Kim, & Cha, 2017). Briefly, anticoagulated blood was centrifuged (50 × g , 10 min) to obtain platelet‐rich plasma (PRP).…”
Section: Methodsmentioning
confidence: 99%
“…The polyacylated sucrose, citric acid, and mumefural derivatives of P. mume showed inhibitory effects on collagen-, arachidonic acid-, and ADP-induced platelet aggregation in vitro (Yoshikawa et al, 2002;Kubo et al, 2005). An herbal mixture of Phyllostachys pubescens leaves and P. mume fruits also showed inhibitory effects on platelet aggregation in vitro (Dong-Seon et al, 2013;Son et al, 2017). In the arteriovenous shunt thrombosis rat model and the carrageenan-induced mice tail thrombosis model, the mixture dose-dependently reduced the weight or length of tail thrombosis, respectively.…”
Section: Cardiovascular Diseasementioning
confidence: 97%
“…The mechanism study showed that the mixture upregulated intracellular cAMP levels, inhibited the release of granule contents containing serotonin, platelet-activating factor (PAF), and thromboxane A2 (TXA 2 ), and decreased the intracellular concentration of calcium ion. The mixture also exerted inhibitory effects by deactivating the collagen receptor glycoprotein VI (GPVI), blocking ligand binding to the receptor, inhibiting the downstream signaling pathway and the ERK activation pathway, and inhibiting the conversion of fibrinogen to fibrin (Dong- Seon et al, 2013;Son et al, 2017). Utsunomiya et al (2002) found that a fruit juice concentrate of P. mume markedly inhibited angiotensin II and H 2 O 2 -induced epidermal growth factor (EGF) receptor transactivation, inhibited ERK activation, and mitigated angiotensin II-induced vascular remodeling.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Bamboo is known to be effective against obesity, and it also relaxes the mind and helps relieve stress, insomnia, and forgetfulness [ 18 , 19 ]. It is also known for its anti-inflammatory, antioxidant, anti-osteoporosis, and anti-wrinkle effects, and it is helpful for hypertension, arteriosclerosis, and activating innate immunity [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%